Tourist destination marketing: From sustainability myopia to memorable experiences. (September 2018) - Hanna, Paul; Font, Xavier; Scarles, Caroline; Weeden, Clare; Harrison, Charlotte
Abstract: This study explores the way in which consumers interpret and process the marketing and communication of sustainable forms of tourism in destinations, in order to inform policy makers about the appropriateness of different types of sustainability messages. Through a thematic analysis of focus group data, we explore the ways in which consumers engage with, and respond to, explicit discourses of sustainability in marketing a tourist destination. We find that overt discourses of sustainability are often rejected by consumers, thus suggesting that messages concerned with sustainability should place greater priority upon consumer experience and opportunities afforded by the purchase and consumption of the travel experience (that happens to be sustainable) they can expect at their chosen destination. As such, commitments to sustainability manifest within organisational philosophy and practice should not drive the principle, overt discourse communicated to consumers. Rather, as embedded within product and practice, such messages would have greater power and effect if they occupied a more subliminal position in destination marketing materials. Highlights: Widens the scope of destination marketing research by focusing on discourses of sustainability. Reveals the ways in which individuals understand and respond to explicit and implicit sustainability messaging. Illustrates how discourses of sustainability are often rejected by consumers. Finds that messages concerned with sustainability should place greater priority upon a consumer experience. Discusses the ways that sustainability marketing has greater power and effect if more subliminal.